2022
DOI: 10.3390/medicina58111568
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Model to Predict Length of Stay and Mortality among Diabetes and Hypertension Inpatients

Abstract: Background and Objectives: Taiwan is among the nations with the highest rates of Type 2 Diabetes Mellitus (T2DM) and Hypertension (HTN). As more cases are reported each year, there is a rise in hospital admissions for people seeking medical attention. This creates a burden on hospitals and affects the overall management and administration of the hospitals. Hence, this study aimed to develop a machine learning (ML) model to predict the Length of Stay (LoS) and mortality among T2DM and HTN inpatients. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…After evaluating the models' performance, we found that Ridge and XGBoost regressions outperformed the others, resulting in lower prediction errors. Our findings align with previous studies, such as Chen and Klasky (2022), which reported similar results with lower prediction errors or loss functions. For instance, they reported the lowest mean absolute error between prediction and actual duration to be around 4 days, while our study showed a similar result of around 6 days.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…After evaluating the models' performance, we found that Ridge and XGBoost regressions outperformed the others, resulting in lower prediction errors. Our findings align with previous studies, such as Chen and Klasky (2022), which reported similar results with lower prediction errors or loss functions. For instance, they reported the lowest mean absolute error between prediction and actual duration to be around 4 days, while our study showed a similar result of around 6 days.…”
Section: Discussionsupporting
confidence: 93%
“…Adopting precise and accurate modeling techniques improves the results and interpretations. In recent years, the prediction of patient LoS for various diseases and scenarios has been extensively explored using a variety of statistical and machine learning methods such as Logistic Regression (LoR), Random Forest (RF), Support Vector Machines (SVM), K-Nearest Neighbors (KNN), decision tree-based methods, among others (Barsasella et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are strengthened by the correlation between the length of time a patient is treated in the ICU and the likelihood of death, especially if the patient spends more than three days in the intensive care unit (Barsasella et al, 2022). The results of this study align with other findings, showing that a longer duration of hospitalization is associated with higher mortality and readmission rates (Rachoin et al, 2020).…”
Section: Introductionsupporting
confidence: 81%
“…The most challenging LOS prediction task is regression-based LOS, where the precise hospitalization LOS as a real value is to be predicted. Barsasella et al [3] investigated a range of classical AI models, such as Decision Trees (DTs), RFs, Logistic Regression (LR), and SVMs for real-valued LOS prediction. While standard ML models work for tabular structured patient data, they neglect the important temporal dependencies between in-hospital patient events.…”
Section: Related Workmentioning
confidence: 99%